2014
DOI: 10.1002/elps.201300574
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and haplotype structure of 24 Y‐chromosomal STR in Chinese Hui ethnic group and its genetic relationships with other populations

Abstract: In the present study, 24 Y-chromosomal short tandem repeat (Y-STR) loci were analyzed in 115 unrelated Hui male individuals from Haiyuan county or Tongxin county, Ningxia Hui Autonomous Region, China, to evaluate the forensic application of the 24 STR loci and to analyze interpopulation differentiations by making comparisons between the Hui group data and previously published data of other 13 populations. A total of 115 different haplotypes were observed on these 24 Y-STR loci. The gene diversities ranged from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Match probability (MP) is computed with computational formula as MP = ∑ p i 2 . Discrimination capacity (DC) is the ratio of total number of distinct haplotypes to the sample size (Zhu et al, ). Furthermore, in order to measure the effect of the newly added loci, forensic parameters of XJM group, such as GD, MP and DC in the newly added loci and five different haplotype sets (AmpFLSTR ® Yfiler ® kit, Promega PowerPlex ® Y23 kit, AmpFLSTR ® Yfiler ® Plus kit, YHRD Maximal, and the kit under investigation) were compared.…”
Section: Methodsmentioning
confidence: 99%
“…Match probability (MP) is computed with computational formula as MP = ∑ p i 2 . Discrimination capacity (DC) is the ratio of total number of distinct haplotypes to the sample size (Zhu et al, ). Furthermore, in order to measure the effect of the newly added loci, forensic parameters of XJM group, such as GD, MP and DC in the newly added loci and five different haplotype sets (AmpFLSTR ® Yfiler ® kit, Promega PowerPlex ® Y23 kit, AmpFLSTR ® Yfiler ® Plus kit, YHRD Maximal, and the kit under investigation) were compared.…”
Section: Methodsmentioning
confidence: 99%
“…Another Y-STR typing kit, GFS Y24, includes 3 Yfiler loci (DYS635 and DYS385a/b), with 21 additional Y-STR loci (DYS531, DYS630, DYS622, DYS552, DYS510, DYS449, DYS459a/b, DYS446, DYS443, DYS587, DYS527a/b, DYS460, Y-GATA-A10, DYS520, DYS557, DYS522, DYS481, DYS570 and DYS444). Previous studies indicated that the additional loci included in these two typing kits have a high level of polymorphisms in Chinese populations [8,10]. In the present study, we investigated haplotype data at the 40 Y-STR loci level of 1128 unrelated male individuals from the following six Chinese ethnic populations: Han (n = 300), Hui (n = 244), Korean (n = 100), Mongolian (n = 100), Uighur (n = 284) and Tibetan (n = 100), using the AGCU Y24 and GFS Y24 STR typing systems (eight loci, DYS449, DYS635, DYS527a/b, DYS522 and DYS444, common to both systems).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of multiplex Y-STR genotyping systems have been developed by several domestic researching groups based on the population data of the Chinese community [8][9][10]. The AGCU Y24 is a domestic Y-STR amplification system that includes Yfiler 17 loci and 7 additional Y-STR loci, five single-copy loci (DYS449, DYS447, DYS522, DYS388 and DYS444) and one multi-copy locus (DYS527a/b).…”
Section: Introductionmentioning
confidence: 99%
“…At present, short tandem repeats (STRs) are widely used in forensic cases for paternity testing and individual identification in worldwide forensic DNA laboratories 1 2 3 4 . The universal use of STRs leads to the establishment of well constructed forensic DNA databases and development of simple typing methodologies.…”
mentioning
confidence: 99%